1995
DOI: 10.4327/jsnfs.48.167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extracts form Hovenia dulcis Thunb. on Alcohol Concentration in Rats and Men Administered Alcohol.

Abstract: The effect of extracts from Hovenia dulcis Thunb. on alcohol (ethanol) concentration after administration of alcohol to rats and men were examined. When a fraction (Fr. G, 0.5g/kg b.w.) extracted from H. dulcis was administered orally to rats 5min before oral administration of alcohol (2g/kg b.w.), the percentage decreases in maximum blood alcohol and acetaldehyde levels were 40% and 37%, respectively, the decreases being larger than those induced by other fractions from H. dulcis. On the other hand, when etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…No significant differences in efficacy were observed between Korea and China H. dulcis extracts [ 34 ]. Similar results were obtained by two other in vivo experiments conducted by Okuma et al [ 35 ] and Chen et al [ 36 ] Both studies showed a decrease of blood alcohol and acetaldehyde levels in rats and mice [ 35 ]. Specifically, the administration of H. dulcis aqueous extract [ 36 ] significantly increased ADH activity in the liver of mice compared to the control group.…”
Section: Pharmacological Activities Of H Dulcis supporting
confidence: 90%
“…No significant differences in efficacy were observed between Korea and China H. dulcis extracts [ 34 ]. Similar results were obtained by two other in vivo experiments conducted by Okuma et al [ 35 ] and Chen et al [ 36 ] Both studies showed a decrease of blood alcohol and acetaldehyde levels in rats and mice [ 35 ]. Specifically, the administration of H. dulcis aqueous extract [ 36 ] significantly increased ADH activity in the liver of mice compared to the control group.…”
Section: Pharmacological Activities Of H Dulcis supporting
confidence: 90%
“…The total amount of sugar exceeds that from general fruits, since it can reach 42 % (Xiang et al 2012). The fruit, seeds, leaves, roots, and bark of H. dulcis are used for medical purposes in some cultures (Okuma et al 1995;Cho et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…The fruit, seeds, leaves, roots, and bark of H. dulcis are all used in traditional Chinese medicine. It is well known for treating liver diseases [8], and several studies have demonstrated that extracts of H. dulcis or its purified compounds can serve as detoxifying agents for alcohol poisoning [8, 9]. In addition, the wood grain is beautiful, and the wood from these hardwood trees is suitable for furniture.…”
Section: Introductionmentioning
confidence: 99%